Butcher : father of modern gyno-psychiatry - Oates, Joyce Carol, 1938- (New York : Alfred A. Knopf, 2024)
"In the 1840s, a young man named Silas Weir begins practicing medicine in Pennsylvania. Though he is considered inept by family, neighbors, and even his mentor, Dr. Weir discovers he has a gift for phlebotomy, treating patients by bleeding them to purify their bodies. But when an experimental procedure goes horribly wrong, Dr. Weir is forced to start over, relocating his family to Trenton, New Jersey, and taking a position at the New Jersey State Asylum for Female Lunatics. There, in the hopes of proving his detractors wrong, Dr. Weir continues practicing dangerous procedures, and soon becomes infatuated with Brigit - a pregnant woman he treats - whom he tries to take her under his wing as an apprentice."--
This is a work of fiction incorporating episodes from the lives of the historic J. Marion Sims, M.D. (1813-1883), "The Father of Modern Gynecology"; Silas Weir Mitchell, M.D. (1829-1914), "The Father of Medical Neurology"; and Henry Cotton, M.D. (1876-1933), Director of the New Jersey Lunatic Asylum, 1907-1930.
Keywords: Human experimentation in medicine -- Fiction; Psychiatric hospitals -- Fiction; Phlebotomy -- Fiction; Physicians -- Fiction; Pregnant women -- Fiction; Pregnant people; Medical fiction